The Influence of Brand Image and Bundling Strategy on Purchase Decisions with Affiliate Marketing as an Intervening Variable: A Study on Wardah Cosmetics Purchases Through Shop Tokopedia - Marini, Faradila Dwi; Mulyanintyas, Dian (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2025)
The development of digital technology and the integration between social media and e-commerce have created new opportunities in marketing strategies, one of which is through affiliate marketing programs. Shop Tokopedia, the result of Tiktok acquisition of Tokopedia, uses this strategy to increase sales, including cosmetic products. On the other hand, the increasing public awareness of beauty has also encouraged the growth of the cosmetics market, so it is an opportunity as well as a challenge for local brands such as Wardah to maintain their market share. This study aims to determine the influence of brand image and bundling strategy on the purchase decision of Wardah cosmetic products at Shop Tokopedia with affiliate marketing as an intervening variable. This study uses a quantitative approach with a survey method through a questionnaire to 100 respondents who have bought Wardah bundling products at Shop Tokopedia. Data analysis was carried out using the Path Analysis technique using Smart PLS 4.0 software. The results of the study show that brand image has a positive and significant effect on affiliate marketing, H1 is accepted. The bundling strategy has a positive and significant effect on affiliate marketing, H2 is accepted. Brand image has a positive and significant effect on the purchase decision, H3 is accepted. The bundling strategy has a positive and significant effect on the purchase decision, H4 is accepted. However, affiliate marketing does not have a significant influence on purchase decisions, so H5 is rejected and cannot be a mediating variable in the relationship between brand image and bundling strategy on purchase decisions. These findings indicate that brand image and bundling strategy are more dominant in influencing purchasing decisions directly than through affiliate marketing.